The effect of filler treatment on the frictional performance of coir dust reinforced polymeric composite. (2021) - Paul, Rajdeep; Gouda, Krushna; Bhowmik, Sumit
Abstract: The article targets to assess the effect of filler treatment on tribological behaviour of coir dust reinforced polymeric composite. Pre-treatment has been done to increases the wear resistant property of the coir particulates. The dust particles are also varied (0, 2.5, 5, 7.5, 10 and 12.5%) for the formulation of the composite. The tribology test is steered at normal load (5, 10 and 20 N), sliding distance (0–1000 m) and constant sliding velocity 100 cm/s. The wear tests are directed by pin-on-disk (POD) machine counter to a dry steel surface. The results revealed that wear presentation of the treated coir filler reinforced polymer composite shows better interfacial bonding compared to the untreated composite and thus improved the tribo-performance of the composite. It was also observed that the coir filler presented a better performance of wear with a lower amount of reinforcement related to the greater quantity of particle mixture. The wear out exteriors of the composites is observed by scanning electron microscope (SEM).